In the valley of the Kauravas: a divine kingdom in the Western Himalaya - Sax, William Sturman (Oxford scholarship online, 2024)
In Western Himalaya, local gods are seen to rule as kings, communicating with their subjects through their human oracles. They remain central in modern society, and 'In the Valley of the Kauravas' explores how the power of the local gods and oracles remains by examining the myths, legends, rituals, and folklore of the region.